The legal and policy contexts of 'revenge porn' criminalisation: the need for multiple approaches. (2nd January 2019) - Kirchengast, Tyrone; Crofts, Thomas
ABSTRACT: The criminalisation of 'revenge porn' offending responds to the non-consensual distribution of intimate images. By smart device or computer, the ability to distribute images assumed to be private across public networks including social media has emerged as a serious twenty-first-century concern. Individual victims present as particularly vulnerable against the ability to disseminate images quickly. It can be a particularly heinous and harmful act, and removal of the offending images may not be guaranteed. Victims have previously been limited to older criminal offences of general application, in addition to civil law remedies ordering the removal of such images. Complexity and expense has often resulted in inaction. This article assesses the Australian context of 'revenge porn' criminalisation, arguing for a range of graduated and complementary responses from self-help to public education to the availability of a range of civil legal remedies and criminalisation.